AGE DIFFERENCES IN PERCEPTIONS OF AUTHENTIC LEADERSHIP - Hadzhiivanova, Milena (E-Journal VFU, 2025)
This study explores age-related differences in the perception of authentic leadership among employees in the Bulgarian business context. A 7-factor model was assessed using an author-developed questionnaire, completed by 255 respondents grouped into five age categories. ANOVA analysis revealed that only the component “Purpose-Driven Leadership” showed statistically significant differences across age groups, with respondents aged 26–35 assigning the highest importance to this dimension. A marginally significant trend was observed for the “Vulnerability” factor, suggesting potential generational sensitivity to openness and authenticity in leadership behavior. Based on these results, an age-sensitive design for an authentic leadership development program was proposed, tailored to the needs and priorities of different generations in the workplace.